Mengembangkan Karakter Peserta Didik yang sesuai Profil Pelajar Pancasila melalui Implementasi Kurikulum Merdeka - Leny Leny (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to develop the character of students according to the Pancasila Student Profile through the implementation of the Independent Curriculum. (1) How the implementation of the independent curriculum can improve the character of students according to the profile of Pancasila students, (2) Factors that can influence the success of developing student character through the independent curriculum. This data collection technique uses a qualitative literature study method. In collecting data by collecting journals from various sources as a comparison. The results of this study are that there is one way to develop the character of students according to the profile of Pancasila students, namely by implementing several learning models such as Project Based Learning and Problem Based Learning learning models that are considered in accordance with the Independent Curriculum. In addition, there are also several factors that support the success of developing student character such as support from the school, competent teachers, parental support and the implementation of a relevant curriculum. Suggestions for further researchers are to go deeper into the collection and processing of data both from library sources or direct observation so that the research results are even better.